The Influence of Service Quality, Corporate Image and Relationship Marketing on The Loyality of Indihome Customers at PT. Telekomunikasi Selular - Reshwara, Aldo; Sumarwan, Ujang; Yuliati, Lilik Noor (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of service quality, corporate image, and customer relationship marketing (CRM) on customer loyalty, mediated by trust, commitment, and satisfaction, in the context of Indihome as the leading fixed broadband provider in Indonesia. The research also seeks to provide managerial recommendations to strengthen customer retention strategies in a highly competitive telecommunications market. A quantitative approach using Structural Equation Modeling (SEM-AMOS) was applied. Data were collected through purposive sampling from 300 Indihome customers via online questionnaires. Validity and reliability were tested with CFA, AVE, and CR. Service quality significantly impacts trust, commitment, satisfaction, and loyalty. Corporate image affects trust, commitment, and satisfaction but not loyalty directly. Satisfaction emerges as the strongest driver of loyalty. This research contributes by examining simultaneously the effects of service quality, corporate image, and CRM on loyalty in the Indonesian fixed broadband industry, a context that has been relatively underexplored. The originality lies in demonstrating that satisfaction and commitment serve as stronger mediators of loyalty compared to trust, challenging prior studies that emphasized corporate image and trust as direct predictors.